2009
DOI: 10.1016/j.neuroscience.2009.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Convergent, not serial, striatal and pallidal circuits regulate opioid-induced food intake

Abstract: Mu opioid receptor (MOR) signaling in the nucleus accumbens (NAcc) elicits marked increases in the consumption of palatable tastants. However, the mechanism and circuitry underlying this effect are not fully understood. Multiple downstream target regions have been implicated in mediating this effect but the role of the ventral pallidum (VP), a primary target of NAcc efferents, has not been well defined. To probe the mechanisms underlying increased consumption, we identified behavioral changes in licking patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 73 publications
(101 reference statements)
6
42
1
Order By: Relevance
“…The effects of NAcc DAMGO on lick microstructure during fatty tastant intake were qualitatively similar to those that occurred during sucrose consumption, which we described in a previous study (41). For both sucrose and Intralipid consumption, hyperphagia induced by DAMGO infusion into the NAcc was associated with increased burst duration, suggesting that palatability-related changes play a central role in increasing consumption after NAcc MOR stimulation, independent of the macronutrient content of the solution ingested.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The effects of NAcc DAMGO on lick microstructure during fatty tastant intake were qualitatively similar to those that occurred during sucrose consumption, which we described in a previous study (41). For both sucrose and Intralipid consumption, hyperphagia induced by DAMGO infusion into the NAcc was associated with increased burst duration, suggesting that palatability-related changes play a central role in increasing consumption after NAcc MOR stimulation, independent of the macronutrient content of the solution ingested.…”
Section: Discussionsupporting
confidence: 83%
“…In some behavioral contexts, DAMGO infusion into the NAcc causes a transient suppression of feeding before subsequent hyperphagia (24,41). However, we found that DAMGOϩsaline infusions resulted in a significant decrease in the latency to begin consumption of high-fat chow [ Fig.…”
Section: Experiments 3: Interactions Of Mor Stimulation In the Nacc Comentioning
confidence: 96%
See 2 more Smart Citations
“…However, each opioid receptor subtype is broadly expressed throughout a multitude of brain regions (13,14), and therefore characterizing the precise opioidergic circuitries that contribute to sodium appetite is an important and ongoing focus of research. Studies in which exogenous opioid receptor agonists are infused into local regions of rat brain have proven informative and, for example, have demonstrated that increased MOR signaling within both the nucleus accumbens and ventral pallidum enhances the hedonic palatability of NaCl (15). However, experiments such as these fail to determine whether such mechanisms act endogenously and are physiologically relevant during sodium deficiency.…”
mentioning
confidence: 99%